2007
DOI: 10.1590/s1517-86922007000400011
|View full text |Cite
|
Sign up to set email alerts
|

Leptina e exercício físico aeróbio: implicações da adiposidade corporal e insulina

Abstract: Obesity currently is qualified as a worldwide health epidemic and its consequences include diabetes mellitus as far as cardiac disease. Genetic and environmental factors contribute to obesity, although the genetic component is still poorly understood in humans. With the cloning of mouse ob gene and its receptor, leptin was discovered, the "satiety hormone". Leptin is expressed and secreted primarily by adipose tissue and is highly correlated to body fat mass. Nevertheless, many factors can regulate leptin synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 76 publications
0
3
0
8
Order By: Relevance
“…A perda do peso corporal provoca a diminuição de leptina plasmática e o aumento, em contrapartida, provoca a elevação da concentração dela. Assim, as concentrações de leptina plasmática sinalizam para o sistema nervoso central (SNC), informando sobre as reservas de energia estocadas em forma de tecido adiposo (negrão;licinio, 2000;MAntzoroS, 2005, BenAtti;lAnchA junior, 2007).…”
Section: Relação Entre Leptina E Atletas De Ginástica Artísticaunclassified
“…A perda do peso corporal provoca a diminuição de leptina plasmática e o aumento, em contrapartida, provoca a elevação da concentração dela. Assim, as concentrações de leptina plasmática sinalizam para o sistema nervoso central (SNC), informando sobre as reservas de energia estocadas em forma de tecido adiposo (negrão;licinio, 2000;MAntzoroS, 2005, BenAtti;lAnchA junior, 2007).…”
Section: Relação Entre Leptina E Atletas De Ginástica Artísticaunclassified
“…Today fat tissue is considered as a very active endocrine organ that is involved in the regulation of metabolism and several hormones' secretion (2,3). A study by the National Cholesterol Control Program's expert panel has shown that obesity, especially abdominal obesity is the most common cause of metabolic disorders such as metabolic syndrome (3,4). Aging process makes elderly women and men more prone to this syndrome due to simultaneous inactivity and increased abdominal visceral fat deposits and reduced muscle mass (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…A study by the National Cholesterol Control Program's expert panel has shown that obesity, especially abdominal obesity is the most common cause of metabolic disorders such as metabolic syndrome (3,4). Aging process makes elderly women and men more prone to this syndrome due to simultaneous inactivity and increased abdominal visceral fat deposits and reduced muscle mass (4,5). Recent findings have shown that obesity, blood lipid disorders, and hypertension are closely associated with adipose tissue secretory function (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Este fato se deve, em grande parte, às mudanças nos hábitos alimentares e ao estilo de vida sedentário, levando ao contínuo aumento do peso corpóreo das populações 3 . Porém, não se pode atribuir esta epidemia de obesidade somente a fatores nutricionais e comportamentais, pois implicaria em desconsiderar a biologia do equilíbrio energético.…”
Section: Introductionunclassified